Japan fund for poverty reduction annual report 2018. (Progress reports of the Japan fund for poverty reduction., 2019)
It includes general information and operational details about the funds two financing modalities project grants and technical assistance. Administered by ADB and established in May 2000, the fund provides direct grant assistance to the poorest and most vulnerable groups in Asia and the Pacific while fostering their long term social and economic development.